Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1007/s11596-012-0008-8
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between serum TSH level with obesity and NAFLD in euthyroid subjects

Abstract: To explore the relationship between serum thyroid stimulating hormone (TSH) level and obesity and nonalcoholic fatty liver disease (NAFLD) in euthyroid subjects, 1322 subjects were subjected to a questionnaire survey and physical examination. Fasting blood samples were collected to test serum TSH, plasma glucose and lipids. Fatty liver was diagnosed by type B ultrasonography. The relationship between serum TSH level and body mass index (BMI), percentage of body fat and NAFLD was analyzed. The results showed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 27 publications
2
31
0
1
Order By: Relevance
“…Eleven articles were excluded (4 articles had no comparison group, 3 articles did not report a subject of interest, and 4 articles did not report an outcome of interest). Fourteen observational studies (9 cross-sectional studies [14,15,16,17,18,19,20,21,22], 4 case-control studies [23,24,25,26], and 1 cohort study [27]) involving 7,191 NAFLD patients and 30,003 controls were included in the meta-analysis. Table 1 describes the detailed characteristics and quality assessment of the included studies.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Eleven articles were excluded (4 articles had no comparison group, 3 articles did not report a subject of interest, and 4 articles did not report an outcome of interest). Fourteen observational studies (9 cross-sectional studies [14,15,16,17,18,19,20,21,22], 4 case-control studies [23,24,25,26], and 1 cohort study [27]) involving 7,191 NAFLD patients and 30,003 controls were included in the meta-analysis. Table 1 describes the detailed characteristics and quality assessment of the included studies.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 5 studies [14,15,16,20,27] involving 26,454 participants, 6 studies [14,15,16,20,23,27] involving 27,070 studies, and 9 studies [14,15,16,17,18,20,25,26,27] involving 32,347 participants were included in our meta-analyses for assessing the association between NAFLD and subclinical hypothyroidism, overt hypothyroidism, and overall hypothyroidism, respectively. NAFLD was not associated with subclinical hypothyroidism (pooled OR = 0.63, 95% CI: 0.18-2.20, p = 0.47, I 2 = 97%, p heterogeneity <0.01), overt hypothyroidism (pooled OR = 1.37, 95% CI: 0.78-2.41, p = 0.27, I 2 = 81%, p heterogeneity = 0.08), or overall hypothyroidism (pooled OR = 1.21, 95% CI: 0.91-1.61, p = 0.18, I 2 = 72%, p heterogeneity = 0.02) compared with non-NAFLD controls (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A large study conducted by the Cleveland Clinic (USA) indicated higher rates of hypothyroidism in NAFLD subjects, compared with the non‐NAFLD group (21.1% vs 9.5%, respectively) . In China, the association between thyroid hormones and NAFLD were studied in euthyroid individuals . Xu et al .…”
Section: Discussionmentioning
confidence: 99%
“…Thyroid function tests additionally confirmed the existence of several thyroid functional abnormalities in patients with chronic liver disease. However, in euthyroid patients, TSH level was not an independent risk factor, and changes in TSH levels did not influence the prevalence of NAFLD [8, 9, 101]. …”
Section: Roles Of Thyroid Hormones and Thyroid Receptors In Liver mentioning
confidence: 99%